2003
DOI: 10.1128/jcm.41.9.4442-4444.2003
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Invasive Serotype VIII Group B Streptococcal Infections in Denmark

Abstract: Serotype VIII group B streptococcus has only rarely been described outside Japan. The Streptococcus Unit, Statens Serum Institut, performed national surveillance of invasive group B streptococcal (GBS) diseases in Denmark in 1999 to 2002 and identified seven clinical GBS isolates of serotype VIII in blood from seven patients admitted to different hospitals

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…In these Danish studies, serotypes Ia, Ib, II, III, and V were predominant, as also observed in the global study by Madrid et al (9). In 2001 and 2002, data from Denmark showed the presence of invasive serotype VIII isolates, which until then were observed virtually only in Japan (12). Since then, all 10 GBS serotypes have been identified in invasive infections in Denmark, although with greatly varying prevalence (13).…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…In these Danish studies, serotypes Ia, Ib, II, III, and V were predominant, as also observed in the global study by Madrid et al (9). In 2001 and 2002, data from Denmark showed the presence of invasive serotype VIII isolates, which until then were observed virtually only in Japan (12). Since then, all 10 GBS serotypes have been identified in invasive infections in Denmark, although with greatly varying prevalence (13).…”
Section: Introductionsupporting
confidence: 64%
“…None of the previous studies on the epidemiology of invasive GBS infections in Denmark (6,(10)(11)(12) provided detailed information on all age groups. In these Danish studies, serotypes Ia, Ib, II, III, and V were predominant, as also observed in the global study by Madrid et al (9).…”
Section: Introductionmentioning
confidence: 99%
“…However, the serotype distribution has shifted somewhat during the past few years [33]. Pregnant Japanese women were found to be predominantly colonized with serotypes VI and VIII [34], whereas invasive disease was being increasingly caused by serotype VIII in a Danish study [35]. Whether this difference is due to geographic predominance or due to the type of infection remains to be determined.…”
Section: Serotype Distributionmentioning
confidence: 97%
“…Thereafter, incidences of its presence began to be described outside Japan. In Denmark, seven instances of invasive disease isolates belonging to CPS VIII among nonpregnant adults were reported from 1999 to 2002 (51). Also, one isolate colonizing a pregnant woman in Maryland was recognized as CPS VIII (52).…”
Section: Serotypingmentioning
confidence: 99%